2010
DOI: 10.1111/j.1475-1313.2009.00707.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and functional influence of surround luminance on the letter contrast sensitivity function

Abstract: Letter contrast sensitivity function depends on surround luminance and this influence should be considered in future standardized directives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 49 publications
2
21
0
2
Order By: Relevance
“…Second, some psychophysical experiments which analyse the influence of surround luminance on contrast sensitivity have been performed by changing the current through the lamps. 11,14 The results obtained in the present experiment confirm the validity of the conclusions obtained in these studies and supports this technique for future research work. Third, the CCT used in our experiment do not cover the range over which fluorescent lamps operate; however, the lighting obtained by dimming tungsten halogen lamps does have a correlated colour temperature similar to that of the low pressure sodium lamp.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Second, some psychophysical experiments which analyse the influence of surround luminance on contrast sensitivity have been performed by changing the current through the lamps. 11,14 The results obtained in the present experiment confirm the validity of the conclusions obtained in these studies and supports this technique for future research work. Third, the CCT used in our experiment do not cover the range over which fluorescent lamps operate; however, the lighting obtained by dimming tungsten halogen lamps does have a correlated colour temperature similar to that of the low pressure sodium lamp.…”
Section: Discussionsupporting
confidence: 93%
“…Technol. 2012; 44: 364-376 of 6.1 mm, which subtended 4.03 min arc at a distance of 5.2 m. Such small letter contrast sensitivity tests have been shown to be particularly sensitive to changes in lighting conditions as well as in ocular visual functionality 14,15,[26][27][28]. Grey shades of letters were chosen so that the Weber contrast decreases in steps of 0.024 log units between consecutive triplets.…”
mentioning
confidence: 99%
“…The device we present here allows an accurate setting of the desired luminance with small deviation from this value over the chart. The device benefits from the masking of the light sources from the observer's view, hence avoiding direct glare (see Apparicio et al 8). The use of this device is therefore advantageous in multi-centre studies, which depend on the collection of data and a comparison of results, and allows accurate follow-up and expert opinion in ophthalmology.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary tests with point sources of light such as halogen spots showed that these are not suitable for testing: apart from pronounced brightness gradients caused by their beam angle characteristics, the directional light causes gloss effects on the silk-matt chart surface. Glare produces a veiling luminance that increments the luminance at the retina 8. It is thus more difficult to recognise weak contrasts.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the contrast resulting from characteristics of the visual stimulus, its background, and lighting conditions needs to be sufficient. Therefore, interestingly, for functional vision in real-life conditions, visual contrast is a function of the available lighting in combination with object characteristics of both the stimulus and its background but, at the same time, an individual's contrast sensitivity is influenced by adaptation to the level of surround luminance (Aparicio et al 2010).…”
Section: Visual Performancementioning
confidence: 99%